Hypertensive Encephalopathy Progressing with the Atypical Findings of Computed Tomography and Magnetic Resonance Imaging - Nural, Mehmet Selim; Baydın, Ahmet; Gökce, Erkan; Nargis, Cemil; Karaoğlanoğlu, Müge (Fırat University, 2007)
Hypertensive encephalopathy is an acute organic cerebral syndrome which occurs when the elevation in the blood pressure exceeds the limit of cerebral vascular auto regulation. Alterations resulting from vasogenic edema affecting cortical and sub cortical white matter areas, especially in the parietal-occipital lobes are observed in the radiological imaging. Involvement of brainstem, basal ganglia and cerebellum is infrequent, if involved it occurs usually in association with the parietal-occipital white matter changes. In this study, clinical, laboratory, computed tomography and magnetic resonance imaging findings of a case with atypical hypertensive encephalopathy involving predominantly the frontal-temporal areas in the radiological evaluations were presented and the differential diagnosis was discussed in the light of literature. ©2007, Firat University, Medical Faculty

Hipertansif ensefalopati kan basıncındaki artışın serebral vasküler otoregülasyon sınırının üzerine çıkması durumunda ortaya çıkan akut organik beyin sendromudur. Radyolojik görüntülemelerde özellikle paryetooksipital bölgelerde kortikal ve subkortikal beyaz cevher alanlarını etkileyen vazojenik ödeme bağlı değişiklikler görülür. Hipertansif ensefalopatide ödeme bağlı değişiklikler sık olmamakla birlikte beyin sapı, bazal ganglion ve serebellum gibi beynin diğer alanlarında görülse de bu değişiklikler genellikle paryetooksipital bölgelerin tutulumu ile birlikte olmaktadır. Burada, radyolojik incelemelerde ağırlıklı olarak frontotemporal alanları etkileyen atipik hipertansif ensefalopatili bir olgunun klinik, laboratuar, bilgisayarlı tomografi ve manyetik rezonans görüntüleme bulguları sunulmuş ve ayırıcı tanı literatür eşliğinde tartışılmıştır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Atipik Bilgisayarlı Tomografi ve Manyetik Rezonans Görüntüleme Bulgularıyla Seyreden Hipertansif Ensefalopati